Exploring the Influence of Parental Financial Behavior, Financial Literacy, and Herding Behavior on Investment Behavior Among Generation Z Investors - Sentosa, Keivo Yakana Kanaka; Gosal, Gladys Greselda (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
This study aims to determine the influence of parents' financial behavior, financial literacy and herding behavior toward investment behavior of Generation Z Investors. The population of this study is management students of Universitas Ciputra Surabaya with a total of 364 respondents. The sample selection method utilized purposive sampling technique. The study was conducted by questionnaires and using Structural Equation Model - Partial Least Square (SEM-PLS). The result of this study showed that Parent Financial Behavior has positive effects on Financial Literacy and not directly affecting Investment Behavior of Generation Z investors in management students of Universitas Ciputra Surabaya but rather having indirect effects through Financial Literacy of the students. This study also shows that Herding Behavior has a positive effect on Investment Behavior of undergraduate management students of Ciputra University Surabaya.